Experimental study of properties for sand bricks with palm oil clinker as a partial replacement for fine aggregate with ratio of 10% with rice husk of 10%, 20% and 30% - Syahira Wahida, Shakrani (2018)
Nowadays construction industry such as material industry continues to emerge significantly in the domestic as well as global market due to increase the population in Malaysia. The brick has been around for centuries and it is the one of the most important component in construction material industry that have highly demand and required more consumption of sand in brick making process. Besides that, there are issues related to waste material such as palm oil clinker and rice husk that have being dumped in landfills without being used.Thus, this experimental study are carry out in concrete laboratory at University of Malaysia Pahang to determine the effectiveness of sand brick production that based on utilization of palm oil clinker and rice husk. The control brick are made from mixture of cement, sand and water. Meanwhile for alternative brick the percentages of sand are replaced by 10% palm oil clinker with rice husk of 10%, 20%, and 30%. The size of the sand brick produced are based on JKR Standard Specifications for Building Works (2005) which is 225 mm X 113 mm X 75 mm. This study is important to analyze the potential of palm oil clinker and rice husk as partial replacement for fine aggregate in sand brick production. Furthermore, this research more focusing on eco-friendly material that can contribute towards sustainability green material. This is because by using this material as replacement of fine aggregate can help reduction of waste. From this research, the test that involved are density test, water absorption test, compressive strength test and flexural strength test.This experimental studies were conducted for 3 days, 7 days, 14 days and 28 days after undergone water and air curing process. Hence, the result testing obtained from alternative brick are compared with control brick. After considering result and discussion all the main objectives are achieved. Therefore, from this research it can summarize that palm oil clinker and rice husk is one of waste material that suitable to be as partial replacement for fine aggregate in sand brick production. The replacement of 10% C + 10% RH is recommended as the best ratio in increases the strength and density of sand bricks compared to replacement of 20% and 30% RH.